Pierre Valentin Boudhors (1754-1831) : un projet de transformation de la prison à Ensisheim - Véronique Umbrecht (In Situ)
In 1806, the prefect of the Haut-Rhin asked the architect of the city of Strasbourg Pierre Valentin Boudhors to draw up plans for the transformation of the beggars' home in the central prison in Ensisheim. The architect fully overhauled the existing building which was intended to gather the convicts from several departments. Trained in Paris, especially in the architect’s office of Chalgrin, he followed the path of the architects of the Revolution, who were considering architecture as a moralising act. The building participated in the education of the citizen and had to show its ethical efficiency: the prison had no other justification than bringing back the convicts into society. Nevertheless, this pedagogy had to be reflected in the development of buildings taking into account the hygiene and moralisation of the place. The architect explained his project in his Preliminary Speech. He carried out a “self-explaining architecture” (“architecture parlante”) while mixing the ancient, medieval and Italian Renaissance architectural elements. Actually, all his drawings were mainly inspired by the Arc-et-Senans saltworks built by Claude Nicolas Ledoux. From the existing buildings, he drew a central axis that symmetrically split the new buildings and organised a succession of yards dedicated to each type of prisoner. Thus, he has designed an architectural complex mixing expression and moralisation.